Building mental health awareness through social media: a qualitative analysis of instagram content strategy - Hutomo Setia Budi; Rendy Iswanto; Evan Raditya Pratomo (Jurnal Konseling dan Pendidikan, 2026)
This study aims to examine how illustration-based visual content on Instagram functions as a communicative strategy for mental health advocacy, community building, and stigma reduction in digital environments. Using a qualitative approach, the research integrates netnography and content analysis to examine posts, visual elements, and audience interactions across selected accounts, including @gemmacorrell, @wantja, @bevscomic, and @zoecainart. These accounts were purposively selected based on their focus on mental health communication and active audience engagement. The findings identify three key patterns: the visual simplification of complex psychological experiences, the use of non-clinical and empathetic communication styles, and the active role of audiences in co-constructing meaning through interaction. These strategies transform abstract emotional states into relatable narratives that foster emotional identification. Audience responses are largely supportive and reflect validation and shared experiences, contributing to stigma reduction. However, most interactions remain affective and rarely develop into deeper critical discussion. This study contributes by shifting attention from psychological outcomes to communicative processes, showing how visual storytelling and participatory interaction shape digital mental health discourse and enable scalable community-based support.